A transformação pela educação: diagnóstico e perspectiva da educação prisional no Instituto Penal Auri Moura Costa. - Oliveira, Othoniel Alves de (2024)
This thesis analyzes the educational assistance implemented at the Auri Moura Costa Women's Prison Institute in the state of Ceará between 2020 and 2022. The research is carried out in the light of the fundamental right to education of persons deprived of their liberty. The main objective is to ascertain how and to what extent the state of Ceará has implemented educational assistance in the state's Women's Prison Institute during the period in question, based on a diagnosis of what happens there, The specific objective is the idea of implementing a program whose main focus in the institution's education is the professional training of incarcerated women, and then for those who progress through the prison conditions or finish serving their sentences to be sent to job vacancies in the local formal labor market. It is not debatable that the state has received from the community the task of imposing penalties on people who have committed criminal acts. The Prison Law Act is clear in providing for re-socialization as the main objective for people serving their sentences. Among the various means made available for the resocialization of prisoners, education is undoubtedly the fundamental right of incarcerated women. Thus, in the light of the fundamental social right to education, it is of great importance to check how the state has carried out its fundamental duty to education in favor of those who have been deprived of their freedom and who are cut off from their community where they have transgressed the rules of social coexistence. In order to achieve the central and specific objectives described, this research work is divided into three chapters. The first chapter looked at education and its fundamental nature in relation to the individual, as well as its implementation for people deprived of their liberty. The second chapter studies the prison system from its origins to the current situation in the Brazilian state. In the last chapter, we sought to dignify what has been happening at the Auri Mora Costa Women's Prison Institute, finally, the idea of implementing a new model of education to prepare women prisoners for the formal job market when they leave behind prison bars is put forward.